Successful treatment of extensive venous thrombosis with combination of immunosuppressants and a direct Xa inhibitor in Behçet's disease. Issue 2 (3rd July 2018) - Hidekawa, Chiharu; Minegishi, Kaoru; Kobayashi, Kouji; Yoshimi, Ryusuke; Kirino, Yohei; Ohno, Shigeru; Takeno, Mitsuhiro; Nakajima, Hideaki
Abstract: Behçet's disease (BD) is a systemic and chronic inflammatory disease of unknown etiology. Vascular involvement can develop in both arterial and venous systems and can cause life-threatening complications. Here, we report a case of vasculo-BD with acute onset of thrombosis in the inferior vena cava (IVC). A 44-year-old woman diagnosed with BD based on recurrent oral aphtha, uveitis and multiple intestinal ulcers for four years, was admitted to our hospital with fever, blurred vision and the right lower abdominal pain. She was positive for HLA-A26 but negative for HLA-B51. Abdominal ultrasonography on admission revealed a thrombosis extending from the bilateral femoral vein to the IVC without intestinal abnormality. Diagnosis of vasculo-BD was made after ruling out other possible diseases. Treatment with rivaroxaban in addition to prednisolone and azathioprine resulted in subsiding of clinical manifestations with the gradual improvement of laboratory data and imaging findings. The present case report suggests a beneficial role of anticoagulation therapy including direct oral anticoagulants for thrombotic lesions of BD patients, in addition to generally recommended immunosuppressive therapy.